PENGARUH UMUR DAN BOBOT POTONG TERHADAP PERSENTASE KARKAS DAN NON KARKAS KERBAU RAWA BETINA DI RUMAH POTONG HEWAN SUMBER REJEKI KABUPATEN CIREBON - , AMINUDIN FUAD ARIF; , Prof. Dr. Ir. Nono Ngadiyono, MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study was conducted to determine the effects of age and slaughter weight on carcass and non carcass of female swamp buffalo at Sumber Rejeki slaughterhouse Cirebon regency. The research material was 64 female swamp buffalos with slaughter weight 250 to 375 kg and 376 to 500 kg, consisted of age 3,5 years and 4 years. Data sollected included of age, slaughter weight, carcass weight, non carcass weight, carcass percentage and non carcass percentage (head, feet, skin, liver, lung, heart, digestive tract and kidney). Data was analysed by analysis of variance of factorial pettern, followed by Duncan Multiple Range Test (DMRT) when there was interaction. The statistic results shawed that the age give influence on the percentage of head 3.5 years of age (8.15 ± 0.60) and the age of 4 years (7.65 ± 0.42), foot cattle aged 3.5 years (2.34 ± 0.30) and 4 years (2.76 ± 0.49), liver of cattle aged 3.5 years (1.13 ± 0.13) and at the age of 4 years (1.45 ± 0.13), lung cattle-lung age of 3.5 years (0.59 ± 0.20) and (age 4 years (0.71 ± 0.05), in the heart of cattle aged 3.5 years (0.31 ± 0.03) and 4 years of age (0.38 ± 0.61), gastrointestinal tract in cattle aged 3.5 years (3.33 ± 0.32) and 4 years (3.83 ± 0.64), and kidney aged 3.5 years (0.27 ± 0.02) and the age of 4 years (0.33 ± 0.07), except for the skin age 3.5 (13.35 ± 0.97) and 4 years (12.76 ± 0.86). The slaughter weight affect the percentage of carcass and weighs 250 to 375 kg (49.41 ± 0.23) and a weight of 376 to 500 kg (49.76 ± 0.06), the percentage of head and weighs 250 to 375 kg (8.24 ± 0.3) and weighs 376 to 500 kg (7.34 ± 0.32), foot and weighs 250 to 375 kg (8.24 ± 0.3) and weighs 376 to 500 kg (7, 34 ± 0.32), skin and weighs 250 to 375 kg (13.58 ± 0.53) and a weight of 376 to 500 kg (12.23 ± 0.83), lung weighs 250 to 375 kg (0 , 62 ± 0.08) and a weight of 376 to 500 kg (0.71 ± 0.08), and heart and weighs 250 to 375 kg (0.33 ± 0.05) and a weight of 376 to 500 kg (0.38 ± 0.05). There was interaction between age and weight on percentage of lungs and head.